Do Explicit Warnings Eliminate the Hypothetical Bias in Elicitation Procedures? Evidence from Field Auctions for Sportscards - List, John A (American Economic Review, 2001)
Do Explicit Warnings Eliminate the Hypothetical Bias in Elicitation Procedures? Evidence from Field Auctions for Sportscards by John A. List. Published in volume 91, issue 5, pages 1498-1507 of American Economic Review, December 2001